PERILAKU WANITA USIA SUBUR (WUS) DALAM PARTISIPASI PROGRAM DETEKSI DINI KANKER PAYUDARA DENGAN PEMERIKSAAN PAYUDARA KLINIS (SADANIS) DI WILAYAH KERJA PUSKESMAS JATINOM : STUDI FENOMENOLOGI - Istianna Nurhidayati; Chori Elsera; Dewi Widayanti (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2018)
Breast cancer is a cancer with prevalence ranked second in Indonesia. Regular checkups are regularly performed as an effort to prevent and detect early cancer. The study aims to explore the meaning and meaning in depth of Women's Age Fertile experience (WAF) in participating in early detection of breast cancer. This research uses qualitative design with phenomenological approach. The number of research samples were 6 participants. The results obtained knowledge of malignant cancer of malignant cancer. The conclusion of this study is the experience of women of childbearing age in the participation of early breast cancer detection programs with different SADANIS - there are some who have a good health awareness and there are feel shy and scared when examined.